Securitisation of mezzanine capital in Germany - Günter Franke; Julia Hein (University of Konstanz, Center of Finance and Econometrics (CoFE), 2007)
A recent trend in the German Asset Backed Securities (ABS) market is the securitisation of subordinated loans and profit participation agreements (PPAs) granted to medium-sized enterprises (MEs). This paper provides an overview of this growing market and analyses the benefits of such transactions for the portfolio companies as well as originators and potential investors. Simulations of ten recent transactions indicate that despite of relatively low interest rates charged on obligors, originators and investors can earn attractive returns at fairly low risk. In particular, the junior tranches of these securitisations exhibit quite attractive risk-return profiles.
urn:nbn:de:bsz:352-opus-116616
Keywords: G10; G21; G24; 330; securitisation; middle market transactions; mezzanine loans; medium-sized enterprises; junior tranche